Importance of Applying Business Ethics To Bakery Small Business - Nurita Andriani; Rita Tri Ariska (Jurnal Studi Manajemen dan Bisnis, 2020)
This research aims to analyze and determine the application of business ethics in the Bakery small business in Sumenep Regency. This study uses qualitative analysis methods, to obtain information carefully with in-depth interview techniques. Observation technique with  direct  observation  in  the  field  is  used  to  support  the  results  of  research.  The application of business ethics is examined in terms of ethical values / morality such as fairness, trust and honesty of the products, customers and employees of the Bakery small business. The study was conducted at Anita Bakery's small business in Sumenep.The results showed that the application of business ethics by Anita Bakery's small businesses in terms of trust and honesty in the product was quite good. This is evidenced by the level of customer loyalty that still persists. The application of business ethics in terms of fairness, trust and honesty towards customer service is quite good, it can be seen from the less complaints, the absence of negative word of mouth communication about the company and consumers are still loyal to the product. The application of business ethics in terms of fairness, trust and honesty towards employees is quite good, this can be seen from the number of employees who last long working in this company. However, it still needs to be considered in the application of business ethics to employees, because the company has not implemented fairness employee recruitment.